Combining Web 2.0 and Web Services in Collaborative Working Environments - Carreras, M. Antonia Martinez; Skarmeta, Antonio F. Gómez (Computing and Informatics, 2012)
Collaborative applications offer significant benefits in business sector. Usually, team members need to use several systems to carry out their tasks. What these users need is an environment which permits them to carry out these tasks automatically, considering the flow of information between the different systems and offering interoperability and composition features. Nowadays, Web Services have gained their prominence in providing these both features. On the other hand, the use of Web 2.0 allows to create web applications in which the user constitutes a key element. What we propose in this paper is the combination of both approaches for creating a Collaborative Working Environment (CWE).